The Settlement at Ialysos and Aegean History с. 1550-1400 B. С. - Furumark, Arne
The Settlement at Ialysos — Minoan and Мусеnaean Expansion in the Aegean Area — The Aegean and the Eastern Mediterranean c. 1550-1450 B. C. (Aegean Influence in the Orient and vice versa — Aegean Elements in Egyptian Tomb Paintings — Alleged Egyptian Names of Aegean Countries — Political and Economic Conditions in the Eastern Mediterranean) — Minoan and Mycenaean Expansion and Interrelations c. 1550-1450 B. C.: Summary and Conclusions.